PENGARUH KOMPETENSI PEDAGOGIK DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA Studi pada Guru SD Negeri di UPT Disdikpora Kecamatan Gringsing,Kabupaten Batang - Sunarso, 12.5202.0096 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to examine the effect of pedagogic competence and motivation to work on teacher performance with the mediation of job satisfaction studies in the Teacher Elementary School in the District Education Office UPT Gringsing, Batang. In this study, the research object is the entire elementary school classroom teachers with the status of civil servants. The entire population of data is grade teacher primary school in the District Education Office UPT Gringsing, Batang numbering 125 people as respondents. Analysis of data using multiple regression method. Techniques of data collection using questionnaires. While the techniques to test if the data validity, reliability testing, test assumptions, multiple regression, F-test, determination test and t test. The results showed that: pedagogical effect on job satisfaction,  work motivation effect on job satisfaction,  pedagogical influence on the performance of teachers,  motivation to work has no effect on teacher performance,  job satisfaction affect the performance of teachers,  job satisfaction does not mediate pedagogical competence influence on teacher performance,  job satisfaction mediates the effect of job motivation on teacher performance. Key Words: Pedagogical Competence, Work Motivation, Job Satisfaction, Teacher Performance.